2011
DOI: 10.1103/physreve.84.046610
|View full text |Cite
|
Sign up to set email alerts
|

Sustained strong fluctuations in a nonlinear chain at acoustic vacuum: Beyond equilibrium

Abstract: Here we consider dynamical problems as in linear response theory but for purely nonlinear systems where acoustic propagation is prohibited by the potential, e.g., the case of an alignment of elastic grains confined between walls. Our simulations suggest that in the absence of acoustic propagation, the system relaxes using only solitary waves and the eventual state does not resemble an equilibrium state. Further, the studies reveal that multiple perturbations could give rise to hot and cold spots in these syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 71 publications
2
46
0
Order By: Relevance
“…This impedes an equal sharing of energy among all grains in the system, hence the long-term dynamics of 1D systems of interacting grains has been described as quasi-equilibrium (QEQ). 40,41,43,44,46,47 To the time scales previously considered in dynamical studies, QEQ was observed to be a general feature of systems with no sound propagation. 40,44 However, recent work has addressed whether QEQ is the final state for such systems.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…This impedes an equal sharing of energy among all grains in the system, hence the long-term dynamics of 1D systems of interacting grains has been described as quasi-equilibrium (QEQ). 40,41,43,44,46,47 To the time scales previously considered in dynamical studies, QEQ was observed to be a general feature of systems with no sound propagation. 40,44 However, recent work has addressed whether QEQ is the final state for such systems.…”
Section: Introductionmentioning
confidence: 97%
“…40,41,43,44,46,47 To the time scales previously considered in dynamical studies, QEQ was observed to be a general feature of systems with no sound propagation. 40,44 However, recent work has addressed whether QEQ is the final state for such systems. 50,51 These studies found that thermalization is indeed possible after very long times, and that the time scale to equilibrium increases with the degree of nonlinearity.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Nesterenko coined the term sonic vacuum to designate this state in a granular chain and demonstrated the existence of solitonic excitations both experimentally and theoretically [2,7,9]. The fate of these strongly nonlinear excitations in amorphous two-or three-dimensional granular media near the (un)jamming transition or in weakly connected polymer networks is only gradually emerging [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%